2015
DOI: 10.1145/2716311
|View full text |Cite
|
Sign up to set email alerts
|

Computing Education in Korea—Current Issues and Endeavors

Abstract: Computer education has been provided for a long period of time in Korea. Starting as a vocational program, the content of computer education for students evolved to include content on computer literacy, Information Communication Technology (ICT) literacy, and brand-new computer science. While a new curriculum related to computer science was established in 2007, the range of computer education being provided in Korean schools has been repeatedly reduced. To identify the cause of this recent phenomenon, we revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…Computational thinking skills are a part of England's state curriculum (Pérez-Marín et al, 2020). In 2018, South Korea added computational thinking skills to the curriculum, including digital literacy, computational thinking, and organizing (Choi et al, 2015). Thus, at the same time, Indonesia should pay special attention to teachers, including science teachers, to increase their self-confidence in these computational thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…Computational thinking skills are a part of England's state curriculum (Pérez-Marín et al, 2020). In 2018, South Korea added computational thinking skills to the curriculum, including digital literacy, computational thinking, and organizing (Choi et al, 2015). Thus, at the same time, Indonesia should pay special attention to teachers, including science teachers, to increase their self-confidence in these computational thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…In this special issue, Gal-Ezer & Stephenson (2014) compared K-12 computer science education in Israel and the U.S., focused on curriculum development, and reported common issues and challenges in areas in curriculum development and teacher training. Choi et al (2015) reported current issues in introducing computer science education in K-12 education in Korea by analyzing education environments, including educational systems, curricula, and teaching environments. This first approach shows the detail of each country's computer education status but does not tell the trends of computer science education.…”
Section: Comparative Education Research On K-12 Computer Science Educationmentioning
confidence: 99%
“…Outros países também tem desenvolvido currículos de computação para a educação básica. Alguns países, como Israel, com larga tradição no ensino médio (Hazzan, Gal-Ezer, & Blum, 2008) e mais recente inserção no Ensino Fundamental II (Bargury et al, 2012), Coreia do Sul (Choi et al, 2015) e Nova Zelândia (Bell, Andreae, & Lambert, 2010), já possuem uma tradição de longo prazo no assunto com uma larga base de materiais didáticos abertos desenvolvidos, como é o caso do Computer Science Field Guide da Nova Zelândia (Bell, 2013). Outros países possuem uma inserção da computação mais recente, como é o caso da Irlanda (Becker & Quille, 2020) e da Argentina (López et al, 2019), mas já possuem materiais didáticos de computação para o ensino médio.…”
Section: Trabalhos Relacionadosunclassified